2020
DOI: 10.3390/metabo10090375
|View full text |Cite
|
Sign up to set email alerts
|

Chasing the Major Sphingolipids on Earth: Automated Annotation of Plant Glycosyl Inositol Phospho Ceramides by Glycolipidomics

Abstract: Glycosyl inositol phospho ceramides (GIPCs) are the major sphingolipids on earth, as they account for a considerable fraction of the total lipids in plants and fungi, which in turn represent a large portion of the biomass on earth. Despite their obvious importance, GIPC analysis remains challenging due to the lack of commercial standards and automated annotation software. In this work, we introduce a novel GIPC glycolipidomics workflow based on reversed-phase ultra-high pressure liquid chromatography coupled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We already demonstrated that different glycolipid classes can be added using the presented glycolipidomics annotation, e.g., for glycosyl inositol phospho ceramides in plants. 59 Hence, our LDA-based annotation strategy is currently the only automated glycolipid annotation software available for the community. Overall, our proposed workflow can be seen as the hallmark for shedding light on the enigmatic processes of gangliosides and glycolipids in general, which are critical mediators in cell−cell interaction and signaling pathways.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We already demonstrated that different glycolipid classes can be added using the presented glycolipidomics annotation, e.g., for glycosyl inositol phospho ceramides in plants. 59 Hence, our LDA-based annotation strategy is currently the only automated glycolipid annotation software available for the community. Overall, our proposed workflow can be seen as the hallmark for shedding light on the enigmatic processes of gangliosides and glycolipids in general, which are critical mediators in cell−cell interaction and signaling pathways.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Our presented open-source annotation workflow based on LDA can be easily applied to any other hyphenated liquid chromatography and MS setup by including new and/or adapting existing decision rules reflecting fragmentation information obtained by (ideally iso-pure) glycolipid standards. We already demonstrated that different glycolipid classes can be added using the presented glycolipidomics annotation, e.g., for glycosyl inositol phospho ceramides in plants . Hence, our LDA-based annotation strategy is currently the only automated glycolipid annotation software available for the community.…”
Section: Discussionmentioning
confidence: 99%
“…and decision rule-based identification (LDA, LipidXplorer, LipidMatch, LipidHunter, etc.). Due to building blocks of lipids leading to a distinct MS2 pattern within the same class, decision rule sets based on well-defined fragments (fragment rules) and their intensity relationships (intensity rules) can be described for specific lipid classes. , For library matching similar principles are applied as in standard metabolomics workflows using accurate mass, MS2 spectra, and scoring algorithm. Both experimental or in-silico databases are applied in lipidomics.…”
Section: Nontargeted Data Analysisincreasing Quality By Multiple Lin...mentioning
confidence: 99%
“…A high-performance liquid chromatography (HPLC) analysis identified the major plant C18 LCBs, including t18:1(Z), t18:1(E), t18:0, d18:1(Z), d18:1(E), and d18:0 ( Chen et al., 2006 ). Plants also contain traces of another four C18 LCBs (d18:2(4E,8E), d18:2 (4E,8Z), t18:2 [with unknown structure], and a unique d18:1 [with a C10=C11 double bond]), one C20 LCB t20:0, and special d21:1 or d22:1 LCBs (the last two LCBs contain a C7=C8 double bond), which have been validated by either mass spectrometry (MS) or nuclear magnetic resonance (NMR) ( Kimberlin et al., 2013 ; Ngo et al., 2020 ; Panzenboeck et al., 2020 ; Wang et al., 2020a ). However, the two common LCBs d20:0 and d20:1, which are detected in animals and Saccharomyces cerevisiae , are rarely reported in plant samples ( De Castro Levatti et al., 2017 ; Zhu et al., 2020 ).…”
Section: Sphingolipid Diversitymentioning
confidence: 99%
“…canaense V.S. Dang IR, UV, HR-ESI-MS, HR-ESI-MS/MS and NMR Panzenboeck et al., 2020 Found four GIPCs containing t18:2 in the Rubus idaeus sample Lactuca sativa var . capitata nidus tenerimma , Spinacia oleracea , Rubus idaeus and Fragaria RP-HRMS/MS using the open-source program LDA for automated GIPC assignment ESI/MS, electrospray ionization MS; ESI-MS/MS, electrospray ionization tandem MS; MS; HPLC/ESI-MS/MS, high-performance liquid chromatography electrospray ionization tandem MS; GC/MS, gas chromatography-MS; MALDI-(Q)-TOF-MS, matrix-assisted laser desorption ionization (quadrupole) time-of-flight MS; UPLC-MS, ultraperformance liquid chromatography-tandem MS; IR, infrared spectroscopy; UV, ultraviolet; HPAEC-PAD, high-performance anion-exchange chromatography with pulsed amperometric detection; HR-ESI-MS/MS, high-resolution electrospray ionization tandem MS; LDA, an open-source software lipid data analyzer.…”
Section: Sphingolipid Diversitymentioning
confidence: 99%